Infant nutrition: "fat" and "skinny". (Journal of Parents and Teachers, 2014)
In our society there is a problem of learning how to eat in a proper way. This article presents an experience and explains the steps and points to follow to teach to nourish and feed properly.
Keywords: Food; nutrition; eating habits.